Soft-Tissue Chondroma in the Preauricular Region: An Unusual Presentation. Issue 1 (March 2018) - Bocchialini, Gabriele; Castellani, Andrea; Bozzola, Anna; Rossi, Alessandro
Chondroma is a benign cartilaginous tumor composed of mature hyaline cartilage and represents only 2.38% of all osteocartilaginous tumors; cases that arise in the preauricular region are rarely found in the literature. This article presents an 80-year-old man with preauricular swelling on the right side and pain with no limitation of joint motion. This patient was evaluated by preoperative clinical manifestation, fine needle aspiration, ultrasound, and magnetic resonance imaging (MRI) scans. The MRI shows a solid lobulated lesion between the masseter muscle and the parotid gland whereas fine-needle aspiration did not provide a diagnosis. Based on these images and the patient's indications and symptoms, a surgical intervention was performed. It is possible to identify three different types of chondromas in the parotid region based on their location. Among the cases of chondroma in the literature, only six originating in the soft tissue of the parotid region have been reported, including this one.